Kepatuhan Pengemudi terhadap Pesan Keselamatan pada Kendaraan - Sodikin Sodikin; Iphan Fitrian Radam (Jurnal Teknologi Berkelanjutan, 2022)
A message that attracts attention and is easy to understand based on the AKC Model will have a compliance impact on the viewer. Likewise, safety messages for drivers can be applied in an effort to improve road safety. Various writings or pictures, especially those on the back of the vehicle, generally attract other drivers who see it. Installation of a distance message on a test vehicle equipped with a camera and the IonRoad Program is used to detect the behavior of the driver or the response of a vehicle following a test vehicle that is installed with a safety message. The results of the analysis show the driver's response when he sees a safety message on the test vehicle and takes action to maintain a safe distance from the test vehicle. The installation of driving safety messages installed on vehicles has the potential to be an alternative in increasing safety in addition to signs or other messages installed above or on the side of the road.